Islam as the religion of the Malaysian Federation: the scope and implications - Ab Aziz, Shamrahayu (International Islamic University Malaysia, 2006)
Article 3(1) of the Federal Constitution declares Islam as the religion of the Federation. Over the years the provisions has given rise to multiple interpretations and endless argument strewn over judicial decisions, academic writings and politicial discussions. This article attempts to highlight and discuss some of the possible implications of the provision, which includes the religious character of the Federation and the special position of Islam, Islamic law and Muslims in Malaysia. These positions may appear to contradict one another but that is the unique character of Malaysian Constitution.